Analysis of the Influence of Planning Management, Human Resources Competency and Budget Disbursement Administration on IAIN Kediri's Budget Absorption - Ilaina, Rudhad (Al-Muraqabah: Journal of Management and Sharia Business, 2025)
IAIN Kediri, with its adequate human resources, especially those related to APBN financial management, still experiences a culture of fast absorption of the budget that has piled up at the end of the year. This study tries to find out whether the theory of the influence of the relationship between planning management, human resource competence, and administration of budget disbursement on budget absorption will have the same effect at IAIN Kediri. This study uses a quantitative method using the multiple regression formula by calculating through SPSS version 26. The results show that from 44 respondents from APBN management officials, from KPA, PPK to procurement officials, it was found that disbursement administration alone had a significant effect on budget absorption in IAIN Kediri in 2022. On the other hand, good planning and competent human resources do not have a substantial impact on budget disbursement at IAIN Kediri if calculated simultaneously. However, if it is calculated partially, it turns out that each of the planning, HR competency, and disbursement administration variables has a significant effect on budget absorption at IAIN Kediri, even though it uses a significance of 10%. Finally, it was found that planning contributed as much as 25.1% influence, human resource competence as much as 28.3%, and completeness of disbursement documents as much as 31.7%.